Bioaccumulation and histopathological alteration of total lead in selected fishes from Manila Bay, Philippines - Sia Su, Glenn L. (Animo Repository, 2013)
This study aims to assess the bioaccumulation of total lead and the effect of heavy metal on the muscles of fish obtained in the coastal lagoon of the Manila Bay. Fish species muscles were assessed for lead concentrations and were examined for histological alterations. Results showed that lead bioaccumulation in the muscles, and a degree of disintegration in the muscle fibers of all the fish examined were found. © 2013 .